(untitled) (Південний архів (історичні науки), 2025)
The purpose of this study is to introduce new sources into scientific circulation regarding the history of Kherson’s municipal self-government in the early 20th century. The document published in this article is a full-text copy of the report by the Governor of Kherson Governorate on the modernization of Kherson’s maritime port in 1908. It provides a detailed characterization of the role of the city’s self-government. The source was preserved in the State Archive of the Kherson Region (F. 1. Chancellery of the Kherson Governor, Op. 1, File 58, 10 sheets). Methodology: In addition to traditional methods of analysis and synthesis, the methodological foundation of this research includes methods of archaeography, following the publication standards for texts from the late 18th to early 20th centuries. Main Findings: The central focus of this study is the report by Kherson Governor Fedor Alexandrovich Bantysh regarding the modernization of Kherson’s port in the early 20th century and the participation of municipal self-government in this process. At the time, such matters were handled by local self-government bodies, but the governor was dissatisfied with their ideological and substantive approach. In his view, the city’s administration pursued modernization in an irrational way, as the planned works made Kherson’s trade dependent on Mykolaiv and Odesa due to the involvement of new railway connections. In his report, the governor personally presented his views to the Minister of Internal Affairs, seeking support for his ideas. He argued that the most effective approach would be to modernize the port in a different way, which would facilitate the transportation of goods and grain from the left bank of the Dnipro. Ultimately, this would enhance the role of Kherson’s port and help it compete with Oleksandrivsk, Mykolaiv, and Odesa. Overall, Bantysh expressed a negative opinion of the municipal administration’s actions. As a result, the document presents a vivid historical narrative of the city of Kherson. Additionally, the document contains numerous statistical data and references to other records that have not survived, providing a comprehensive picture of power relations at various levels – central, regional, and municipal.